IMPACT OF DEPRESSION ON PSYCHOLOGICAL WELLBEING OF PATIENTS CAREGIVERS IN FEDERAL NEUROPSYCHIATRIC HOSPITAL IN BARNAWA, KADUNA STATE - Adamu, Magdaline Gajere; Shekwolo, David Markus; Atafo, Denis`; Doka, Jerry James (African Journal of Social and Behavioural Sciences, 2024)
The caregiving role is often associated with various challenges, and understanding the psychological consequences is crucial for developing effective support systems. Therefore, this study investigated the influence of depression and stress on the psychological wellbeing of caregivers providing support to patients at the Federal Neuro-Psychiatric Hospital in Barnawa, Kaduna. A total of one hundred and twenty mental health patient care givers in FNPH Barnawa, caregivers (males = 54 and females = 57) aged between 18 and 58 years, with a mean age of 36.16 years and an average age of 9.457 years, were selected. Two instruments were used in this study: the Self-Rating Depression Scale (SDS) developed by Zung (1965) and the Brief Psychological Wellbeing Scale developed by Ryff (1995). The descriptive statistics used and inferential statistics were used to test the hypothesis. The Pearson correlation results revealed a statistically significant negative relationship (r(109)= -0.583, P < 0.05) between depression and psychological well-being among caregivers. The study concluded that there is a significant negative relationship between depression and the psychological well-being of patients’ caregivers and recommended that the ministry of health should establish caregiver support groups within the hospital where caregivers can share their experiences and receive emotional support from others facing similar challenges.